2014
DOI: 10.1017/s0022215114001285
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid – a useful drug in ENT surgery?

Abstract: To date, the benefits of tranexamic acid as a prophylactic treatment to reduce the rate and severity of post-tonsillectomy bleeding are less certain. Two recently published pilot studies looking at primary haemorrhage in children and secondary haemorrhage in adults following tonsillectomy suggest that further large, randomised trials should explore the efficacy of tranexamic acid in routine ENT surgery. There are potential reductions in patient morbidity and cost savings if tranexamic acid is found to be effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
20
0
2
Order By: Relevance
“…The most common adverse effects of tranexamic acid are gastrointestinal, including postoperative nausea and vomiting, but the incidence of those effects was low. With intravenous administration, a rapid bolus injection can cause significant hypotension . In this study, intraoperative blood pressure and the incidence of postoperative emesis showed no significant difference between the treatment group and the control group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The most common adverse effects of tranexamic acid are gastrointestinal, including postoperative nausea and vomiting, but the incidence of those effects was low. With intravenous administration, a rapid bolus injection can cause significant hypotension . In this study, intraoperative blood pressure and the incidence of postoperative emesis showed no significant difference between the treatment group and the control group.…”
Section: Discussionmentioning
confidence: 48%
“…With intravenous administration, a rapid bolus injection can cause significant hypotension. 30 In this study, intraoperative blood pressure and the incidence of postoperative emesis showed no significant difference between the treatment group and the control group. Many studies have suggested that up to 15 mg/kg by intravenous infusion can be recommended in surgical procedures, 9 and the adverse effects of tranexamic acid are dose-dependent and uncommon at that recommended dose.…”
Section: Discussionmentioning
confidence: 50%
“…Sie ist deshalb im Routinefall verzichtbar. ▶ Die Gabe von Tranexamsäure, systemisch und topisch, bewirkt eine Blutungsreduktion um 30-40 % [149][150][151][152][153]. Die Qualität des Operationsgebietes verbessert sich [153].…”
Section: Vorbereitung Des Operationsgebietesunclassified
“…Hence it can be omitted in routine cases. The application of tranexamic acid, systemic or topical, leads to reduced bleeding by 30–40% [ 150 ], [ 151 ], [ 152 ], [ 153 ], [ 154 ]. The quality of the surgery site improves [ 154 ].…”
Section: Principles and Basics Of Endonasal Sinus Surgerymentioning
confidence: 99%